“Silent” mitral cells dominate odor responses in the olfactory bulb of awake mice - Kollo, Mihaly (2014)
How wakefulness shapes neural activity is a topic of intense discussion; in the awake olfactory bulb, high activity with weak sensory-evoked responses were reported in mitral/tufted cells (M/TCs). Using blind whole-cell recordings, we find 33% of M/TCs to be “silent”, yet showing strong sensory responses - with weak or inhibitory responses in “active” neurons. Thus, a previously missed M/TC subpopulation can exert powerful influence over the olfactory bulb.